Consumers’ Purchasing Intent Regarding Conventional, Plant-Based, and Cultured Meats - Marlee Stollar; Joy N Rumble; Emily B. Buck; Annie R. Specht; Wuyang Hu; C. Lynn Knipe (Journal of Applied Communications, 2022)
In today’s market, there are a growing number of meat options, from conventional to plant-based to cultured meat. As a result, agricultural and food companies need to understand what influences consumer purchases in order to communicate about these options and understand future changes in the marketplace. This study surveyed a \ sample of Ohio consumers (n = 1,250) 18 and older, which was matched to the state population. Data were collected on the Theory of Planned Behavior (TPB) attributes of consumer attitudes toward purchasing, subjective norms, and perceived behavioral control to understand purchasing intent toward conventional, plant-based, and cultured meats. Descriptive results of these TPB attributes showed significant differences between meat options. The biggest difference was observed between the subjective norms of conventional and cultured meat. Additionally, logistic regression showed consumers’ current and future purchasing intent, with conventional meat, to be most affected by subjective norms. Current and future buying intent of plant-based meat, and future buying intent of cultured meat, was found to be most affected by consumers’ attitudes. The food and agricultural industry should use this information to better shape advertising and messaging with consumers about meat options. For conventional meat, agriculturalists should pay attention to consumer interests and perhaps include some social elements in advertising since it is influenced by subjective norms. Further research should explore all attributes of TPB with consumer purchasing intent, but especially with attitudes and subjective norms.
Keywords: Consumer Meat Preferences; Theory of Planned Behavior; Conventional Meat; Plant-Based Meat; Cultured Meat